Representación pictórica de las vendedoras ambulantes en la ciudad de Loja, en la corriente postimpresionista-expresionista - Moreno Suquilanda, Marlon Israel (2018)
The present investigation of artistic proposal is of theoretical-practical character since a referential study is made, to conclude in a well-founded pictorial proposal. The main objective is to study the post-Impressionist-expressionist current to make a pictorial representation of street vendors in the city of Loja. For this it is required to interpret in a plastic way the artistic knowledge about human figure, natural drawing and movement in the popular characters of the proposed theme, the characteristics of women are studied, the expression of the faces, the clothing they use, natural light , the colors that are reflected in the figure of each of them to maintain a chromatic and compositional richness; In addition, the works of Vincent Van Gogh will be studied considering as one of the artistic references, to achieve an interesting and subjective pictorial proposal.